La Aplicación De Estrategias Metodológicas En El Inter Aprendizaje Y Su Incidencia En La Motivación De Los Estudiantes De La Unidad Educativa “Quintiliano Sánchez Rendón”, Del Cantón Buena Fe, Provincia De Los Ríos. - Sinchiguano Toapanta, Miryam (2015)
The present titled investigation work: The application of methodological strategies in the one inter learning and their incidence in the motivation of the students of the Educational Unit "Quintiliano Sánchez Rendón, of the canton Good Faith, County of The Ríos, arose of the necessity of knowing what it is happening to the use of the teaching strategies in the classrooms of classes, since many students demonstrate little attention and interest in learning and it is for this reason that they are not able to reach a good academic yield. Explaining the concept of the variables one can say that: The methodological strategies are tools that use the educational ones so much with the students for a learning. The inter learning is built between two or more subject to sharing knowledge, activities and space-times. The motivation is that that impels a person to carry out certain actions and to persist in them until the execution of its objectives, we also link it with the will and the interest. The specific objectives that thought about in the investigation are: To investigate on the methodological strategies of inter-learning that are using the educational ones in the students; to know if motivation exists in the students, when carrying out the learning activities in the classroom and to Investigate on the motivation models to motivate the students. It was interviewed to a sample of 175 students and 12 educational of the facility, the same ones that allowed to obtain the conclusions and recommendations on the outlined problem.